Atributinių junginių modeliai Mikalojaus Daukšos „Postilėje“ ir Antano Baranausko tarmių tekstuose - Vasiliauskienė, Virginija (Baltistica, 1998)
PATTERNS OF THE ATTRIBUTE PHRASE IN DAUKŠA’S „POSTILĖ“ AND DIALECTAL TEXTS COMPILED BY ANTANAS BARANAUSKASThe placement of the adjective, the participle and the genitive attribute in a noun phrase is very similar both in 1) „Punktai sakymų“ and Daukša’s „Postilė“ (postposition is more frequent; the influence of Latin and Polish is evident, especially in the case of the genitive pronoun) and 2) in Bretkūnas’ „Postilė“ and dialectal texts compiled by Baranauskas (preposition is more frequent; the placement of the genitive noun varies).Similar features could be found in „Punktai sakymų“ and dialectal texts.But the patterns of the attribute phrase constituents in Old Lithuanian differ in certain cases from those of Modern Lithuanian: (a) the position of the genitive attribute was less strictly determined in Old Lithuanian; (b) the adjective more frequently follows the head noun than in Modern Lithuanian; (c) the postposed genitive and the adjective attribute in some cases may have a more prominent stress only; (d) very often enclitics occupy second position in the sentence.These conclusions initiated further research into the attribute phrase (K. Lukauskas’ „Sermons” (18th c.) and the didactic prose of the 19th c.) because the data obtained did not reveal any change in the attribute phrase word order.Preliminary results enable us to put forward several hypotheses, the most important of these is as follows: in written works the standard attribute phrase with the preposed adjective and the postposed genitive noun (actually its placement was not determined) has been preserved for almost 300 years.
Keywords: sintaksė; atributiniai junginiai; senieji raštai